1982
DOI: 10.1177/004051758205200110
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Prototype Firefighter Protective Clothing: Heat Dissipation Characteristics 1

Abstract: Continuing efforts to develop new firefighter protective clothing have resulted in an advanced prototype garment demonstrating improved dissipation of metabolic heat under laboratory exercise conditions. The performance of three variations of the advanced prototype design were compared to standard turn-out gear and tested for heat retention. Analysis of biophysical data obtained from four volunteer subjects revealed heat loss advantages associated with the innovative design and fabric characteristics of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…13 Conclusions showed improved ventilation in the arm and back regions, but no significant improvement in the chest or leg regions of the prototypes tested. 13 The authors suggested increasing the number of ventilation openings in the coverall legs to increase heat loss and consider the addition of vertical ventilation openings in the trousers of firefighter turnouts. 13 A study which evaluated the opening and closing of the sleeve and pant cuffs, opening of the collar, and the replacement of a belt with suspenders, also found positive results for heat loss.…”
Section: Ventilation In Structural Firefighter Turnoutsmentioning
confidence: 92%
See 2 more Smart Citations
“…13 Conclusions showed improved ventilation in the arm and back regions, but no significant improvement in the chest or leg regions of the prototypes tested. 13 The authors suggested increasing the number of ventilation openings in the coverall legs to increase heat loss and consider the addition of vertical ventilation openings in the trousers of firefighter turnouts. 13 A study which evaluated the opening and closing of the sleeve and pant cuffs, opening of the collar, and the replacement of a belt with suspenders, also found positive results for heat loss.…”
Section: Ventilation In Structural Firefighter Turnoutsmentioning
confidence: 92%
“…13 This study included shortening the coat, opening the collar, adding ventilation openings and spacers throughout the coat and pants, and increasing the collar height. 13 Conclusions showed improved ventilation in the arm and back regions, but no significant improvement in the chest or leg regions of the prototypes tested. 13 The authors suggested increasing the number of ventilation openings in the coverall legs to increase heat loss and consider the addition of vertical ventilation openings in the trousers of firefighter turnouts.…”
Section: Ventilation In Structural Firefighter Turnoutsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over-protecting firefighters from external heat can not only be costly but also potentially dangerous. Several researchers have investigated material selection [ l 3] and garment design [14] to attempt to reduce water vapor resistance of the firefighter tunic. Much of this research was precipitated by a U.S. requirement to incorporate a vapor barrier into the tunic; such a requirement is almost absent in Europe.…”
Section: Fire Environmentmentioning
confidence: 99%
“…Many of researches for thermal protective clothing were focused on heat protective performances [4][5][6][7][8][9] and thermal comfort properties [10][11][12]. Thermal protective clothing has tended to be evaluated by the effectiveness of its heat-resistance ability.…”
Section: Introductionmentioning
confidence: 99%